Learn more about

Refine search

Results (displaying matches 1-50 of 2967) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
604.a.9664.2 604.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 + x^2 - x\) $\mathrm{USp}(4)$ 0
971.a.971.1 971.a \(y^2 + y = x^5 - 2x^3 + x\) $\mathrm{USp}(4)$ 1
976.a.999424.1 976.a \(y^2 + (x + 1)y = x^6 - 2x^5 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 0
997.b.997.1 997.b \(y^2 + y = x^5 - 2x^4 + 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1051.a.1051.1 1051.a \(y^2 + y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1091.a.1091.1 1091.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1145.a.1145.1 1145.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
1205.a.1205.1 1205.a \(y^2 + y = x^5 + 2x^4 - x^2\) $\mathrm{USp}(4)$ 1
1207.a.1207.1 1207.a \(y^2 + (x^2 + x + 1)y = -x^5 - x^4\) $\mathrm{USp}(4)$ 1
1269.a.1269.1 1269.a \(y^2 + (x^3 + x^2 + x + 1)y = x^2 + x\) $\mathrm{USp}(4)$ 1
1327.a.1327.1 1327.a \(y^2 + (x^2 + x + 1)y = x^5 + 2x^4 + x^3\) $\mathrm{USp}(4)$ 1
1397.a.1397.1 1397.a \(y^2 + y = x^5 - x^3\) $\mathrm{USp}(4)$ 1
1403.a.1403.1 1403.a \(y^2 + y = x^5 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 1
1415.a.1415.1 1415.a \(y^2 + (x^2 + x + 1)y = x^5 - 3x^4 + x^3 - x\) $\mathrm{USp}(4)$ 1
1416.b.135936.1 1416.b \(y^2 + (x^3 + x)y = -2x^4 - x^3 + x + 1\) $\mathrm{USp}(4)$ 0
1499.a.1499.1 1499.a \(y^2 + (x^3 + 1)y = -x^5 + x^2 - x\) $\mathrm{USp}(4)$ 1
1595.a.231275.1 1595.a \(y^2 + (x^3 + x)y = x^4 - x^3 + 2x^2 - 4x + 1\) $\mathrm{USp}(4)$ 1
1637.a.1637.1 1637.a \(y^2 + y = x^5 - x^4 + x^3 - x^2\) $\mathrm{USp}(4)$ 1
1643.a.1643.1 1643.a \(y^2 + y = x^5 + x^4 - 5x^3 + 5x^2 - 2x\) $\mathrm{USp}(4)$ 1
1655.a.1655.1 1655.a \(y^2 + (x^3 + x^2 + x)y = x^3 - x\) $\mathrm{USp}(4)$ 1
1706.a.3412.1 1706.a \(y^2 + (x + 1)y = x^6 - x^5 - x^4\) $\mathrm{USp}(4)$ 1
1757.a.1757.1 1757.a \(y^2 + (x^3 + x^2 + x + 1)y = x^3 + x^2\) $\mathrm{USp}(4)$ 1
1797.a.5391.1 1797.a \(y^2 + (x^2 + x + 1)y = x^5 - 4x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ 1
1811.a.1811.1 1811.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 - x\) $\mathrm{USp}(4)$ 1
1835.a.1835.1 1835.a \(y^2 + y = x^5 - 4x^3 + 5x^2 - 2x\) $\mathrm{USp}(4)$ 1
1876.a.7504.1 1876.a \(y^2 + (x^2 + 1)y = x^5 - x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1919.a.1919.1 1919.a \(y^2 + (x^3 + 1)y = x^3 + x^2\) $\mathrm{USp}(4)$ 1
1961.a.1961.1 1961.a \(y^2 + (x^3 + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 1
1991.a.1991.1 1991.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 1
2031.a.6093.1 2031.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x\) $\mathrm{USp}(4)$ 1
2059.a.2059.1 2059.a \(y^2 + y = x^5 - 4x^4 + 4x^3 - x\) $\mathrm{USp}(4)$ 1
2061.a.6183.1 2061.a \(y^2 + (x^3 + 1)y = -x^4 - x\) $\mathrm{USp}(4)$ 1
2075.a.10375.1 2075.a \(y^2 + (x^3 + 1)y = -2x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
2085.a.6255.1 2085.a \(y^2 + (x^2 + x + 1)y = -x^6 + 2x^4 - x^2\) $\mathrm{USp}(4)$ 1
2101.a.2101.1 2101.a \(y^2 + y = x^5 - x^4\) $\mathrm{USp}(4)$ 1
2243.a.2243.1 2243.a \(y^2 + y = x^5 - 3x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 1
2290.a.4580.1 2290.a \(y^2 + (x^3 + 1)y = -2x^4 + 4x^2 - x - 2\) $\mathrm{USp}(4)$ 1
2295.a.11475.1 2295.a \(y^2 + (x^2 + 1)y = 5x^5 - 2x^4 + x^3 - x\) $\mathrm{USp}(4)$ 1
2301.a.6903.1 2301.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 - x\) $\mathrm{USp}(4)$ 1
2309.a.2309.1 2309.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^4 - x\) $\mathrm{USp}(4)$ 1
2345.a.2345.1 2345.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 - x^2 + x\) $\mathrm{USp}(4)$ 1
2349.a.2349.1 2349.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 - x\) $\mathrm{USp}(4)$ 1
2357.a.2357.1 2357.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 1
2405.a.2405.1 2405.a \(y^2 + x^2y = x^5 + 4x^4 - 8x^2 - x + 4\) $\mathrm{USp}(4)$ 1
2507.a.2507.1 2507.a \(y^2 + y = x^5 - 2x^4 + 3x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2528.a.161792.1 2528.a \(y^2 + xy = 8x^5 + 27x^4 + 25x^3 - x^2 - 6x + 1\) $\mathrm{USp}(4)$ 1
2542.a.5084.1 2542.a \(y^2 + (x + 1)y = x^5 - 2x^4 + 3x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2547.a.7641.1 2547.a \(y^2 + (x^3 + 1)y = x^4 + x\) $\mathrm{USp}(4)$ 1
2563.a.2563.1 2563.a \(y^2 + (x^2 + x + 1)y = -x^5 - 2x^2 - x\) $\mathrm{USp}(4)$ 1
2592.a.5184.1 2592.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - x^2 - x\) $\mathrm{USp}(4)$ 1
Next

Download all search results for